CD4 Depletion or CD40L Blockade Results in Antigen-Specific Tolerance in a Red Blood Cell Alloimmunization Model - Natarajan, Prabitha; Liu, Dong; Patel, Seema R.; Santhanakrishnan, Manjula; Beitler, Daniel; Liu, Jingchun; Gibb, David R.; Liepkalns, Justine S.; Madrid, David J.; Eisenbarth, Stephanie C.; Stowell, Sean R.; Hendrickson, Jeanne E. (Frontiers in Immunology, 2017)
Approximately 3-10% of human red blood cell (RBC) transfusion recipients form alloantibodies to non-self, non-ABO blood group antigens expressed on donor RBCs, with these alloantibodies having the potential to be clinically significant in transfusion and pregnancy settings. However, the vast majority of transfused individuals never form detectable alloantibodies. Expanding upon observations that children initially transfused with RBCs at a young age are less likely to form alloantibodies throughout their lives, we hypothesized that “non-responders” may not only be ignorant of antigens on RBCs but instead tolerized. We investigated this question in a reductionist murine model, in which transgenic donors express the human glycophorin A (hGPA) antigen in an RBC specific manner. Whereas wild type mice treated with poly IC and transfused with hGPA RBCs generated robust anti-hGPA IgG alloantibodies that led to rapid clearance of incompatible RBCs, those transfused in the absence of an adjuvant failed to become alloimmunized. Animals depleted of CD4+ cells or treated with CD40L blockade prior to initial hGPA RBC exposure, in the presence of poly IC, failed to generate detectable anti-hGPA IgG alloantibodies. These non-responders to a primary transfusion remained unable to generate anti-hGPA IgG alloantibodies upon secondary hGPA exposure, and did not prematurely clear transfused hGPA RBCs even after their CD4 cells had returned or their CD40L blockade had resolved. This observed tolerance was antigen (hGPA) specific, as robust IgG responses to transfused RBCs expressing a third party antigen occurred in all studied groups. Experiments completed in an RBC alloimmunization model that allowed evaluation of antigen specific CD4+ T cells (HOD: hen egg lysozyme, ovalbumin, and human duffyb) demonstrated that CD40L blockade prevented expansion of ovalbumin 323-339 specific T cells after HOD RBC transfusion, and also prevented germinal center formation. Taken together, our data suggest that recipients may indeed become tolerized to antigens expressed on RBCs, with the recipient’s immune status upon initial RBC exposure dictating future responses. Though questions surrounding mechanism(s) as well as sustainability of tolerance remain, these data lay the groundwork for future work investigating RBC immunity versus tolerance in reductionist models and in humans.